The Black Swan: The Impact of the Highly Improbable - Nassim Nicholas Taleb (USA Random House, 2010)
A black swan is an event, positive or negative, that is deemed improbable yet causes massive consequences. In this groundbreaking and prophetic book, Taleb shows in a playful way that Black Swan events explain almost everything about our world, and yet we-especially the experts-are blind to them. In this second edition, Taleb has added a new essay, On Robustness and Fragility, which offers tools to navigate and exploit a Black Swan world.
Keywords: Nonfiction; Philosophy; Business; Finance; Economics; Psychology; Forecasting; Uncertainty (Information theory)